Investigating Errors in the Written Composition of Undergraduate ESL Learners at Aligarh Muslim University - Khan, Mohd Akram (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2023)
This study investigated common English writing errors made by undergraduate ESL learners at Aligarh Muslim University whose first language is Urdu-Hindi. The study is carried out with the help of written compositions from 20 participants. The data were analyzed within a broader framework propounded by S. Pit Corder. The researcher concluded that the study's errors were in the form of spelling, copula, word choice, prepositions, verb tenses, plural formation, punctuation, subject-verb agreement, and articles. The reasons behind these errors were identified as interlingual and intralingual causes, whereas intralingual was the most significant factor, which indicates their inadequate knowledge about grammar. The findings of the study were spelling (19.35%), copula (14.51%), word choice (12.90%), prepositions (11.29%), verb tenses (9.67%), plural formation (19.13%), punctuations (8.60%), subject-verb agreement (8.06%) and articles (6.45%). So, based on above data analysis the most common type of errors was spelling that is 19.35% and the least common one was article that is 6.45%.,. The findings of the study have implications for the researchers of scientific papers, especially in the realm of English as a Second Language learning.